Utilization and determinants of follow-up colonoscopies within 6 years after screening colonoscopy: prospective cohort study - Hoffmeister, Michael; Stock, Christian; Brenner, Hermann (International journal of cancer, 2019)
Previous studies have reported that repeat colonoscopies were often not conducted in the recommended time interval after screening colonoscopy. We prospectively followed participants of screening colonoscopy from Germany for 6 years to investigate utilization and determinants of repeat colonoscopies. In a longitudinal study on the effectiveness of screening colonoscopy in the state of Saarland (Germany), participants who had a screening colonoscopy between 2005 and 2007 were contacted by mail 6 years after screening and requested to fill in a standardized questionnaire on utilization of repeat colonoscopies. For all colonoscopies reported, colonoscopy and histology reports were requested from the physician(s). Of 6,407 screening participants, 2,212 (35%) have utilized another colonoscopy. Among participants with negative findings at screening (no adenomas), 962 (22%) had a subsequent colonoscopy within 6 years from screening, accounting for 43% of all patients with a repeat colonoscopy. Family history of CRC and detection of hyperplastic polyps were found to be determinants of higher repeat colonoscopy use. As many as 44% of the participants with low-risk adenomas (N = 509) and 39% with high-risk adenomas (N = 290) at screening did not utilize surveillance colonoscopy within 6 years. Utilization was better with higher school education, prior cancer screening participation and if high-risk adenomas were detected, lower among current smokers and lowest among participants ≥70 years. New strategies will be required considering determinants of adherence to avoid unnecessary colonoscopies and to improve utilization of surveillance according to recommended time intervals among patients at higher risk of CRC in the future.
First published: 11 September 2018
Gesehen am 13.02.2019